Antidepressant use in Australia and Sweden—A cross‐country comparison. Issue 4 (9th November 2020) - Eek, Emma; van Driel, Mieke; Falk, Magnus; Hollingworth, Samantha A.; Merlo, Gregory
Abstract: Purpose: To compare the dispensed use of antidepressants in Australia and Sweden. Methods: We analysed publicly available data from Australia and Sweden on dispensed use of antidepressants from 2006 to 2018. Results: The dispensed use of antidepressants has increased in both Australia and Sweden. Australia had a more rapid increase resulting in a higher total use. The utilisation profile was similar in both countries; SSRIs were the most commonly used group, "other antidepressants" were the group that increased the most, and seven of the eight most used substances were the same. There were differences in which antidepressants were most used, with the three most prescribed antidepressants being escitalopram, sertraline, and venlafaxine in Australia; and mirtazapine, sertraline, and citalopram in Sweden. Conclusion: Dispensed use of antidepressants has increased remarkably in both Australia and Sweden between 2006 and 2018. Although similar with regard to economic status and health care system, use of antidepressants differs between both countries. This may be a result of a combination of factors related to medical, contextual and policy evidence. The differences displayed in this study may reflect varying accessibility of treatments, national programmes enhancing mental health literacy in the population, clinical prescribing guidelines and timing of approval of new antidepressants.